2013
DOI: 10.1093/swr/svt017
|View full text |Cite
|
Sign up to set email alerts
|

Race, Relationships, and Trust in Providers among Black Patients with HIV/AIDS

Abstract: A trustful patient-provider relationship is a strong predictor of positive outcomes, including treatment adherence and viral suppression, among patients with HIV/AIDS. Understanding factors that inform this relationship is especially relevant for Black patients, who bear a disproportionate burden of HIV morbidity and mortality, and may face challenges associated with seeing providers of a racial/ethnic background that is different from their own. Using data collected through the Enhancing Communication and HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 31 publications
2
27
0
Order By: Relevance
“…Experienced providers are more accepting of individuals with various medical issues and additional clinical experiences allow them to deliver standardized care, regardless of the client’s background. This is consistent with the finding that being older is related to higher levels of provider–client interaction, which can be explained by older providers having greater provider–client trust, being considered to be more experienced, and being more aware of the clients’ needs (Earl et al, 2013). Experience working with drug users might help providers to develop knowledge and skills that make it easier to treat such clients more effectively.…”
Section: Discussionsupporting
confidence: 88%
“…Experienced providers are more accepting of individuals with various medical issues and additional clinical experiences allow them to deliver standardized care, regardless of the client’s background. This is consistent with the finding that being older is related to higher levels of provider–client interaction, which can be explained by older providers having greater provider–client trust, being considered to be more experienced, and being more aware of the clients’ needs (Earl et al, 2013). Experience working with drug users might help providers to develop knowledge and skills that make it easier to treat such clients more effectively.…”
Section: Discussionsupporting
confidence: 88%
“…Clinics with discourteous staff and complicated appointment scheduling and referral processes may deter patients from returning [21]. While, providers who gain patients' trust, are responsive, display empathy, and provide individualized care can encourage both retention and adherence among patients [21, 41, 42]. In an analysis of patient perceptions of provider attitudes, those with a gap in care of more than one year were more likely to perceive that the provider didn't listen carefully to them or disliked caring for HIV-infected people [43].…”
Section: Barriers and Facilitators To Retention And Adherencementioning
confidence: 99%
“…Saha [34] reported that greater "cultural distance" between providers of HIV care and patients living with HIV was associated with disparities that appeared not to be based on race or ethnicity. However, non-White patients had lower levels of trust, adherence to antiretroviral therapies, and lower rates of viral suppression [57]. Additional research should examine neighborhood and community-level factors that may contribute to HIV and other disparities.…”
Section: Discussionmentioning
confidence: 99%